Bilateral retinal microglial response to unilateral optic nerve transection in rats. (17th December 2015) - Cen, L.P.; Han, M.; Zhou, L.; Tan, L.; Liang, J.J.; Pang, C.P.; Zhang, M.
Highlights: Unilateral ON transection leads to long-term bilateral microglial responses. ON transection results in changes of ipsilateral microglial density and morphology. ON transection leads to microglial morphology alternation in contralateral retina. Abstract: When retinal ganglion cells undergo apoptosis after optic nerve (ON) injury, microglial cells proliferate and promptly clear the degenerated debris in the ipsilateral retina. However, microglial changes in the contralateral retina have not been fully elucidated. This study characterized the long-term bilateral retinal microglial responses after unilateral ON transection. We analyzed the time course of proliferation and morphology changes of microglial cells, between 3 days and 12 weeks post ON transection, of undisturbed and reactive microglia in bilateral retinas of adult Fischer rats with unilateral ON transection. Microglia in retinas without ON transection were distributed homogeneously and possessed a highly ramified morphology, as judged by immunohistochemistry for ionized calcium-binding adapter molecule 1 (Iba1). After ON transection, microglia density in the ipsilateral retina increased gradually from 3 days to 2 weeks, and decreased from 3 weeks to 12 weeks, along with dramatic inverted alteration of process branch points of microglia in the ganglion cell layer (GCL). Transformation of ramified microglia into ameboid-like macrophages with few branching processes was observed in the ipsilateral retina from 1 week to 3 weeks. Though an increase in microglial density was weak in the contralateral retina and could only be statistically detected in the central retina, the morphological alteration over time was obvious and similar to that of the ipsilateral retina. In the inner plexiform layer (IPL), cell density and morphological changes of microglia in both the ipsilateral and contralateral retina were not prominent. These findings indicates that, though proliferation of microglial cells is weak in the contralateral retina after unilateral ON transection, conspicuous alterations in microglial morphology occur bilaterally. These suggest that using the contralateral retina as a control in studies of retinal degeneration should be considered with caution.